KEDUDUKAN HUKUM WHISTLE BLOWER DALAM PERSPEKTIF HUKUM PIDANA DI INDONESIA - Hasbi, Mhd. (LPPM Universitas Ekasakti Padang, 2023)
One of the efforts made by the state in order to realize legal protection for every citizen is to carry out honest and fair law enforcement, including the state's efforts to and overcome the occurrence of criminal acts that can disrupt public security and public order. Current criminal law enforcement practices This is known as a new term, namely whitsle blower. Etymologically whitsle blower comes from the word whitsle which means